1999
DOI: 10.1007/s11745-999-0385-5
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐influence of membrane polyunsaturated fatty acids and hypoxia‐reoxygenation on α‐ and β‐adrenergic function of rat cardiomyocytes

Abstract: The purpose of the present investigation was to determine whether the beneficial effects of polyunsaturated fatty acids (PUFA) may influence ischemia-reperfusion-induced alterations of myocardial alpha- and beta-adrenoceptor (alpha-AR, beta-AR) responsiveness. This study was carried out using monolayer cultures of neonatal rat ventricular myocytes in a substrate-free, hypoxia-reoxygenation model of ischemia. The cardiomyocytes (CM) were incubated during 4 days in media enriched either with n-6 PUFA (arachidoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 36 publications
2
11
0
Order By: Relevance
“…Hypoxia reduces heart rate in adult and perinatal atrial strips [51][52][53] and cardiomyocytes [54][55][56] , suggesting that a bradycardic response to hypoxia is intrinsic to adult and perinatal cardiac cells. However, the effect of hypoxia has not been assessed in the early fetal heart.…”
Section: In Isolated Fetal Hearts Hypoxia Induces Bradycardia Which mentioning
confidence: 99%
“…Hypoxia reduces heart rate in adult and perinatal atrial strips [51][52][53] and cardiomyocytes [54][55][56] , suggesting that a bradycardic response to hypoxia is intrinsic to adult and perinatal cardiac cells. However, the effect of hypoxia has not been assessed in the early fetal heart.…”
Section: In Isolated Fetal Hearts Hypoxia Induces Bradycardia Which mentioning
confidence: 99%
“…Another adipokine, tumor necrosis factor-α (TNFα) is released as a consequence of inflammatory responses and acts as an autocrine/paracrine signal to regulate the function of other adipokines, insulin and other critical metabolic factors [16]; TNFα contributes to insulin resistance and diabetes, and the adipose inflammatory response is thought to play a significant role in obesity [3,45]. In turn, systemic changes in lipid metabolism and adiposity affect the composition of synaptic membranes within the brain, altering the function of the neurotransmitter receptors and signaling molecules that are embedded in the lipid milieu [6,12,14,19,31]. This may explain why the synaptic and behavioral effects of early-life organophosphate exposure do not represent simply the continuing effects of initial damage, but rather evolve over an extended period from juvenile stages through adolescence and adulthood [37,41,43], concurrently with the emergence of metabolic dysfunction and changes in weight and adiposity [20,21,33].…”
Section: Introductionmentioning
confidence: 99%
“…Alterations in the lipid composition of neural membranes affects neuronal activity, receptor and signaling function, and synaptic transmission [11,20,22,25,32], effects that are likely to contribute to the success of a ketogenic diet in treating intractable epilepsies [8,13,23,24], to pilot studies showing beneficial effects in attentional disorders and autism [13,16,33], and to results in animal models of behavioral deficits [50]. In our earlier work, we found that consumption of a high fat diet in adulthood was able to offset most of the cholinergic synaptic deficits caused by neonatal parathion exposure [37], while at the same time incurring metabolic liabilities [26].…”
Section: Discussionmentioning
confidence: 99%
“…The effects of a high-fat diet on synaptic responses are likely due to global changes in the composition of synaptic membrane lipids [22,32], and therefore can span multiple brain regions and neurotransmitter systems [11,20,25]. In the present work, we explored the lasting effects of neonatal parathion exposure on serotonin (5-hydroxytryptamine, 5HT) pathways in rat brain regions and the effects of dietary manipulation in adulthood on the outcome.…”
Section: Introductionmentioning
confidence: 99%